1937
DOI: 10.1037/h0057431
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral states during sleep, as studied by human brain potentials.

Abstract: The general recording arrangements for taking long continuous ink records on an 8 ft drum are similar to those described in our previous paper. The three new sets of amplifiers, installed during the year, were designed to give stable and constant amplification over long runs and to have a long 'time constant,' in order to record faithfully relatively slow changes in the potentials. They were also designed not to block when large surges occur. Each of the three circuits is completely independent so that the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
0
21

Year Published

1944
1944
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 696 publications
(260 citation statements)
references
References 22 publications
4
220
0
21
Order By: Relevance
“…Moreover, we tried to control for this effect by excluding EEG recordings with signs of sleep deeper than stage A of Loomis (1937) and by controlling for the time of day of the recording.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we tried to control for this effect by excluding EEG recordings with signs of sleep deeper than stage A of Loomis (1937) and by controlling for the time of day of the recording.…”
Section: Discussionmentioning
confidence: 99%
“…In a last step the already corrected EEG was visually inspected by an experienced neurophysiologist who was blind to the patient's symptoms. He cut further artefacts not readily removed in steps 1 and 2 from the EEG recording: muscle, movement and electrode artefacts; patients with EEGs containing deeper sleep than stage A of Loomis et al (1937) and with EEGs that showed EEG-identifiable pathologies (e.g. generalized epilepsy) were excluded.…”
Section: Artefact Rejectionmentioning
confidence: 99%
“…Traces of 7.0 to 7.5 per second frequencies were found in the records of 125 out of the series of 500 subjects, but only in 4 individuals was there more than 5 per cent of such slow activity in the 2-minute recording; of these 4 individuals, 1 had 19 per cent slow activity, 2 had 9 per cent, and 1 had 6 per cent.…”
Section: Methods Of Analyzing the Recordsmentioning
confidence: 99%
“…In the earlier years, many researchers used variants of the Dement and Kleitman standard [8] to stage sleep automatically. Itil et al [9] used period analysis to classify 1-min epochs based on the Loomis et al [10] classification. Johnson et al [11] presented a spectral analysis study of the EEG in different stages which was subsequently used by Larsen and Walter [12] to develop an automated staging technique based on multiple-discriminant analysis.…”
Section: Introductionmentioning
confidence: 99%